PENGARUH TUTUPAN LAHAN DAN CURAH HUJAN TERHADAP SIFAT FISIK TANAH SERTA DEBIT MATA AIR DI HUTAN CEMPAKA, PASURUAN, JAWA TIMUR - Utami, Rossi Widhi; Lestariningsih, Iva Dewi; Wicaksono, Kurniawan Sigit; Anggara, Akmaludin Dimas; Lathif, Sarifudin (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Climate change causes forest fires that impact land cover damage, which can cause damage to soil properties and disrupt hydrological characteristics such as loss of spring or discharge depletion. This study aimed to assess the influence of land cover and rainfall on soil physical properties and spring discharge in the Cempaka Forest area. The study was conducted on three land covers, i.e., shrubs, pine, and non-timber forest products (NTFPs) in the Cempaka Forest area, Curah Tangkil Block, Pasuruan Regency, East Java Province. The measured parameters were soil bulk density, permeability, porosity, infiltration, daily rainfall, and spring discharge. Data analysis used analysis of variance (ANOVA) test at a 5% level, correlation test, and regression. The results showed that differences in land cover had no significant effect on soil physical properties. The correlation and regression results between rainfall and spring discharge showed that rainfall influenced spring discharge by 4%. The correlation and regression results in the medium-heavy rainfall categories influenced spring discharge by 38%.